Acute effects of multi-ingredient pre-workout dietary supplement on anaerobic performance in untrained men: a randomized, crossover, single blind study - Aleksander Drwal; Tomasz Pałka; Lukasz Tota; Szczepan Wiecha; Pavol Čech; Marek Strzała; Marcin Maciejczyk (BMC, 2024)
Abstract Background Multi-ingredient pre-workout dietary supplements (MIPS), which are combinations of different ingredients acting on different physiological mechanisms, can have a synergistic effect and improve performance. The aim of the study was to determine the acute effects of a multi-ingredient pre-workout supplement containing: beta-alanine, taurine, caffeine, L-tyrosine, and cayenne pepper (capsaicin) on anaerobic performance. Methods A randomized, crossover, single-blind study was designed. Twelve young, healthy, untrained men aged 22.4 ± 1.44 years participated in the study. The participants performed a supramaximal all-out test (20 s Wingate test) twice, day by day, in random order: test after placebo or MIPS consumption. In both trials, the following variables were measured in the exercise test: total work performed, peak power, mean power, time to reach peak power, and power decrease. Results MIPS was found to be effective in improving peak power (p = 0.009, ES = 0.77) and mean power (p = 0.04, ES = 0.62) in the Wingate test. However, the supplement consumption did not affect the amount of total work done (p = 0.10, ES = 0.48) in the test or power decrease (p = 0.07, ES = 0.53). The data indicate, that the improvement in anaerobic power was due to a significant improvement in pedaling speed, which was manifested in a significant improvement (i.e. shortening) in time to peak power (p = 0.003, ES = 0.88). Conclusion A multi-ingredient pre-workout dietary supplement was found to be effective in improving Wingate (anaerobic) performance. Trial registration NCT06363669, retrospectively registered on 11.04.2024 (ClinicalTrials.gov).